The Pterophoridae fauna of Khakassia Republic and south of Krasnoyarsk region (Russia) (Insecta: Lepidoptera) - Per Ya. Ustjuzhanin; Roman E. Maksimov (SHILAP, 2023)
The article gives a faunal list of Pterophoridae species of Khakassia Republic and the south of Krasnoyarsk region. We have examined 41 localities, as a result of which, 24 species are reported for this region for the first time. In total, 40 Pterophoridae species are currently known for the Republic of Khakassia and for the south of Krasnoyarsk region.